2001
DOI: 10.1073/pnas.051626298
|View full text |Cite|
|
Sign up to set email alerts
|

Immunization of metastatic breast cancer patients with a fully synthetic globo H conjugate: A phase I trial

Abstract: The carbohydrate antigen globo H commonly found on breast cancer cells is a potential target for vaccine therapy. The objectives of this trial were to determine the toxicity and immunogenicity of three synthetic globo H-keyhole limpet hemocyanin conjugates plus the immunologic adjuvant QS-21. Twenty-seven metastatic breast cancer patients received five vaccinations each. The vaccine was well tolerated, and no definite differences were observed among the three formulations. Serologic analyses demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
134
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(140 citation statements)
references
References 25 publications
3
134
0
3
Order By: Relevance
“…This vaccine is currently in phase 3 clinical trials, and the GH epitope is manufactured by the programmable one-pot method (26). Although GH-specific IgM was generated in most patients, the level of IgG was low, and patients often reported inflammatory response at the injection site with occasional systemic complaints such as fever, arthralgias, and myalgias (18). All these undesirable symptoms are similar to the reported side effects of QS21 (27)(28)(29).…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…This vaccine is currently in phase 3 clinical trials, and the GH epitope is manufactured by the programmable one-pot method (26). Although GH-specific IgM was generated in most patients, the level of IgG was low, and patients often reported inflammatory response at the injection site with occasional systemic complaints such as fever, arthralgias, and myalgias (18). All these undesirable symptoms are similar to the reported side effects of QS21 (27)(28)(29).…”
mentioning
confidence: 53%
“…GH is also expressed weakly in normal tissue but only restricted to apical epithelial cells at lumen borders, a site that seems to be immune-inaccessible (9,(15)(16)(17). Moreover, higher levels of anti-GH Ab were detected in the plasma of breast cancer patients (18)(19)(20). Our previous study also revealed that the expression of some glycans, such as GH and Stage-specific embryonic antigen 3 (SSEA3) (also called Gb5), was observed on breast cancer cells and breast cancer stem cells (BCSCs) (21).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Among the larger studies, the relative risk estimates appeared to decrease by approximately 0.09 for each additional birth (Weir et al, 2007) . Cohort life-table studies of white Catholic nuns have demonstrated the greater mortality due to cancers of the breast and lower mortality due to cancer of the uterine cervix (Gilewski, 1998). Case control studies have indicated pregnancies to be more numerous among controls than among breast cancer patients (Gajalakshmi and Shanta, 1991;Gajalakshmi et al, 1998;2009;Rao, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been established that the serum of breast cancer patients contains high levels of antibodies against the Globo H epitope, and this epitope is also targeted by the monoclonal antibodies MBr1 (5-7) and VK-9 (8). As a result, this hexasaccharide has been the focus of studies aimed at anticancer vaccine development (9)(10)(11)(12)(13)(14)(15). Many elegant syntheses of Globo H have been reported (11,(16)(17)(18)(19)(20)(21)(22)(23)(24), including one approach that uses the one-pot programmable oligosaccharide synthesis developed in our laboratory (25).…”
mentioning
confidence: 99%